2022
DOI: 10.3390/jpm13010040
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccines during Pregnancy and Breastfeeding: A Systematic Review

Abstract: Background: Pregnant and breastfeeding women received unclear recommendations regarding COVID-19 vaccination at the beginning of the pandemic, as they were not included in the initial clinical trials. This systematic review aims to provide an update regarding COVID-19 vaccines during pregnancy and breastfeeding. Methods: The systematic review was carried out through a literature search in Medline/Pubmed. Studies were selected if they included information regarding COVID-19 vaccination during pregnancy and brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…A recent study stated that when the pre-alpha strain was predominant in Spain, all pregnant patients with SARS-CoV-2 infection in their cohort were unvaccinated, the rate of hospital admission was 6.6%, and progression to severe COVID-19 disease was 2.2% [ 29 ]. Several studies revealed that COVID-19 vaccination should be strongly recommended to pregnant women to decrease the risk of severe COVID-19 [ 29 , 30 , 31 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study stated that when the pre-alpha strain was predominant in Spain, all pregnant patients with SARS-CoV-2 infection in their cohort were unvaccinated, the rate of hospital admission was 6.6%, and progression to severe COVID-19 disease was 2.2% [ 29 ]. Several studies revealed that COVID-19 vaccination should be strongly recommended to pregnant women to decrease the risk of severe COVID-19 [ 29 , 30 , 31 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The binding of the virus to ACE2 receptors reduces their dynamics on alveolar epithelial cells and activates the host’s adaptive immune response. Many inflammatory markers (mainly interleukin IL-1β, IL-4, IL-10, and interferon γ) are released, which disrupt the integrity of endothelial cells and thus hinder the vesicular-capillary barrier, often causing severe hypoxemia [ 7 , 26 ]. It seems that immune system adaptations during pregnancy may affect the response profile after vaccination against COVID-19.…”
Section: Covid-19 During Pregnancy and Breastfeedingmentioning
confidence: 99%
“…Pregnant women are not given “live” vaccines [ 8 , 45 ]. Table 2 presents vaccinations recommended for pregnant and breastfeeding women, taking into account local recommendations [ 8 , 9 , 10 , 26 ].…”
Section: Recommendations For Vaccination Of Pregnant Women – Prioriti...mentioning
confidence: 99%
See 2 more Smart Citations